La escuela para padres y su influencia dentro del comportamiento actitudinal de los niños y niñas de 3 a 5 años en la escuela Vicente Miranda de la provincia de Pichincha, cantón Mejía, parroquia Alòag en el año lectivo 2014 -2015 - Nato Chicaiza, Rocío Consuelo (2015)
The present research work has as a main objective making a parents school, where their selves be involved on their children’s daily activities, applying different techniques and strategies as; workshops, video conferences, tests, etc. which ones will help to achieve familiar aspects, getting more quality parents time. On this thesis where applied different methods for making better family relations focus on values, rights and obligations for girls and boys fulfillment. At the same way infants will be improve their attitude into class room with partners and teachers creating an integral personal formation and the importance that it has on the society.